Relatos de vida contextualizados como estrategia para mejorar la escritura en los estudiantes del grado 8-4 de la Institución Educativa del Dagua en el año 2019 (2020)
In the Educational Institution of Dagua headquarters Gym, the object of study is grade 8-4 where there are permanent difficulties based on communicative academic activities, these related to coherence, cohesion, syntax, semantics, spelling, textual plan and identification of elements and structure of the narrative in a text. Situation it is evidenced in a low performance in the different areas of knowledge as well as in the results of the knowing Tests. In order to solve these difficulties, the theories of some authors like Cassany (1999), Castillo & Orozco (2017), Méndez (2013), Benejam & Quinquer (2000), among others, illustrated how, through experiences and its vivences, students can improve writing and apply this learning in their different written productions. In such a way this proposal was based on constructivism as a navigation chart in the Institution and with a meaningful learning methodology. To achieve this purpose, a qualitative approach was used, taking as a reference the case study in which the observation and description of the different assigned activities predominated. Thanks to the applied strategy, the students improved their academic results and their written competence was assertive. Also, the principles of meaningful learning articulated with the experience of the teacher formulated an action plan for the teaching and learning of writing linked to contextualized life stories. These results were recorded in a digital book that was published on the internet where the life stories were compiled. Keywords: writing, narration and stories, context.